Empirical analysis of the compressive strengths of composite materials the case of rice straw and cement - Manaloto, John Arvin R. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/7342/6431